ANALISIS CRACK PADA WORK ROLL ROUGHING MENGGUNAKAN METODE MAGNETIC PARTICLE TESTING DAN ULTRASONIC TESTING DI PT. XYZ - Reza Mahendra (2020)
In the steel making industry has several flow schemes from the ongoing production process so as to produce quality steel products. The flow scheme of the production process that takes place includes 'direct reduction plant, blast furnace, steel billet plant, slab steel plant, hot strip mill, wire rod mill, and cold rolling mill. Hot strip mill is the production process of making thin steel sheets namely coil, plate, and sheet through the heating temperature reaches ± 1250 ºC, and is an advanced processing of sheet steel produced from the steel slab process, and then performs hot rolling (milling). To meet the target of thin sheet steel production at PT. XYZ, the tools used are always operating every day. Due to the tools that have very high operating hours, inspection activities on the equipment are very important so that the tools can still operate properly and optimally. Some methods for analyzing cracks are magnetic particle test and ultrasonic test. The results of the research with magnetic particle test and ultrasonic test methods show that the process of roasting or heat treatment by the slab to work roll roughing at an uneven temperature of 1150 ºC caused the death of the rotating motor at the work roll roughing stops more than three minutes above the roll table so it does not can be rolled back. Causing the work roll to crack (crack).